Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Pegawai - Sri . Utami; Muhammad Harlie; Muhammad Zainul (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Leaders have an important task in managing human resources. A leader must realize that employees are the asset that most influences the company's productivity. In other words, it must be realized that there is a dependency between the company and its employees. The role of a leader in influencing decisions directed towards organizational goals greatly determines the direction of the company's progress regarding the way or style a person leads in managing their company according to the specified direction.